Development of a pulling machine to produce micron diameter fused silica fibres for use in prototype advanced gravitational wave detectors. (16th July 2018) - Toland, K; Conway, A; Cunningham, L; Hammond, G; Hennig, J; Hild, S; Hough, J; Jones, R; Momany, E; Perri, L; Rowan, S; Cumming, A
Abstract: A pivotal aspect in increasing the sensitivity of the Advanced LIGO detectors to allow the first gravitational wave detection, GW150914, was the installation of the monolithic fused silica suspensions. The 40 kg test mass suspended by four 400 μ m fused silica fibres lowers the thermal noise as compared to initial LIGO. There is a desire for the use of thinner fibres to suspend smaller optics for other experiments of interest to the gravitational wave community that the current aLIGO fibre pulling machine is not capable of. We present here an overview of a new CO2 laser-based micron scale diameter fibre pulling machine developed at the University of Glasgow, based on the principals of our current aLIGO fibre pulling machine. We also discuss the upgraded fibre characterisation apparatus for dimensional and strength testing. It was found that fibres with a minimum diameter between 7.6 and 9.3 μ m had an average breaking stress of 2.7 GPa and a Young's modulus value of 63.3 GPa, which is lower than the accepted bulk value of 72 GPa. Fibres with an average diameter between 13.2 and 17.8 μ m had higher breaking stress and Young's modulus values ranging between 3.7–4.0 GPa and 71.8–75.9 GPa, respectively.